Rapid adsorption of ternary dye pollutants onto copper (I) oxide nanoparticle loaded on activated carbon: Experimental optimization via response surface methodology. Issue 2 (June 2016) - Agarwal, S.; Tyagi, I.; Gupta, V.K.; Bagheri, A.R.; Ghaedi, M.; Asfaram, A.; Hajati, S.; Bazrafshan, A.A.
Graphical abstract: Surface textural property of adsorbent and optimized parameters. Highlights: Ternary adsorption of dyes on copper (I) oxide nanoparticle loaded on activated carbon. We demonstrate a methodology for simultaneous dyes removal from aqueous solution. Application of ultrasound accelerates mass transfer and decreases the removal time. Abstract: Rapid adsorption of hazardous anionic dyes sunset yellow (SY), eosin B (EB) in the presence of cationic dye i.e. methylene blue (MB) from ternary solutions using copper oxide nanoparticle loaded on activated carbon(Cu2 O-NP-AC) was well investigated and elucidated. The synthesized adsorbent was well characterized using various analytical techniques such as X-ray diffraction (XRD), and FE-SEM. The impact of effective parameters such as pH, sonication time, adsorbent dosage and initial dye concentration was well studied and optimized using central composite design superimposed with response surface methodology. The numerical optimization revealed that the optimum removal (>96.0%) for all dyes were achieved using of 0.025 g, 25, 15and15 mg L −1 of SY, EB and MB after 4 min sonication at pH of 5.0 at above conditions. The adsorption equilibirium and kinetic data was well fitted and found to be in good agreement with Langmuir and pseudo-second order respectively. The maximum adsorption capacities SY, EB and MB were 113, 137 and 110 mg g −1, respectively.